Nomenclatural synopsis of the new Calea ser. Candolleanae (Asteraceae: Neurolaeneae), a clade endemic to Eastern and Central Brazil - Bueno, Vinicius R.; Silva, Gustavo H. L.; Reis-Silva, Genilson A.; Teles, Aristônio M.; Nakajima, Jimi N.; Gostel, Morgan R.; Heiden, Gustavo (Phytotaxa, 2024)
Molecular phylogenetic reconstruction of Calea demonstrated that the circumscription of infrageneric groups should be altered or that the description of new sections and series is necessary for recognition of monophyletic taxa. One of these infrageneric groups is C. ser. Candolleanae, newly proposed here. Previously recognized as an informal complex, this group comprises eight species that occur exclusively in Brazil. Most of its species can be characterized by long-pedunculate radiate capitula, campanulate involucre, epaleaceous or partly paleaceous receptacle, strigose or glabrous cypselae, and pappus scales 0.1–1.5 mm long. In order to improve our understanding of this series, we generated a nomenclatural synopsis, revising protologues and type material. We propose 6 lectotypifications and 1 neotypification. In addition, we record new Brazilian state level occurrences for three species: C. angusta (Alagoas), C. gardneriana (Maranhão), and C. martiana (Bahia).